Optimasi Kemampuan Komunikasi Anak Berkebutuhan Khusus dengan Aplikasi Comm-Screen - Nur Fahmi, Rumaysha; Maulidiyah, Ardiyati; Ikhfa Humaira, Frizky; Siswanto, Arif (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Background: Communication needs in children with special needs (ABK) are absolute things to strive for as optimally as possible. One speech therapy approach in facilitating these needs is alternative & augmentative communication (AAC). The development of AAC offers great potential to improve the effectiveness of nonverbal CwSN (Children with Special Needs) communication. Based on surveys, AAC is most widely used for patients with non/minimal verbal such as ASD (Autism Spectrum Disorders) or other conditions. Objective: this study aims to develop a mobile application-based AAC media innovation called Comm-Screen. Method: research is carried out quantitatively with tiered surveys and literature studies to design a prototype of the Comm-Screen application. The Comm-Screen application can display symbols (images) and output audio (sounds) that have been adapted to the culture and speech therapy interventions in Indonesia. The Comm-Screen application is also designed based on appropriate interventions and has been studied in the speech therapy profession to treat communication disorders in nonverbal CwSN. Results: From 54 respondents, 97% of them realized the importance of application-based AAC media in Indonesia as one of the preferred methods for learning communication for nonverbal CwSN. 97.7% of respondents stated that the Comm-Screen application prototype is effectively used as a medium for nonverbal CwSN communication intervention in Indonesia. Conclusion: There is hope from speech therapy practitioners for the advancement of AAC media with the Comm-Screen application that can meet the criteria and objectives of speech therapy interventions in Indonesia. Improvements and development of Comm-Screen applications are still needed as the need for future interventions increases. Keywords: AAC, Communication, Nonverbal, Speech therapy